A Hybrid Perovskite Solar Cell Modified With Copper Indium Sulfide Nanocrystals to Enhance Hole Transport and Moisture Stability (Solar RRL 8∕2017). Issue 8 (August 2017) - Ma, Yingzhuang; Vashishtha, Parth; Shivarudraiah, Sunil B.; Chen, Kai; Liu, Ye; Hodgkiss, Justin M.; Halpert, Jonathan E.
Abstract : Lead halide perovskite solar cells have attracted tremendous attention for their impressive power conversion efficiencies. However, long‐term lifetime is the main issue holding back the commercialization of perovskite solar cells. Here, Ma et al. (article No.201700078 ) present a dual‐function layer consisted of copper indium sulfide quantum dots, acting as both the hole transporting layer and the moisture blocking layer for perovskite solar cells. These quantum dots could be easily deposited on the perovskite layer, thus avoiding changing the existing efficient charge transfer system. Meanwhile, these nanocrystals construct a hydrophobic barrier to humidity, encapsulating the perovskite layer. This post‐deposition alteration to the perovskite film could improve the device stability, especially under high humidity. These results indicate that adding a quantum dots layer is a simple way to improve perovskite stability without sacrificing the device performance.